2014
DOI: 10.3109/15412555.2014.908833
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Abnormalities and Carotid Atherosclerosis in Ex-Smokers without Airflow Limitation

Abstract: It is well-established that COPD patients have a burden of vascular disease that cannot be fully-explained by smoking history but the mechanistic links between atherosclerosis and pulmonary disease in COPD patients are not well-understood. Moreover, in ex-smokers without symptoms or other evidence of COPD, subclinical pulmonary and vascular disease, although potentially present, has not been described or evaluated. Hence our aim was to use sensitive three-dimensional (3D) pulmonary and carotid imaging to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Most of earlier studies showed lower FEV 1 was associated with thicker IMT 3,5,8,15,18 and the presence of subclinical atherosclerosis, 3,7,10,15 However, a small study by Pike et al of 61 subjects without airflow limitation found that FEV 1 was not associated with IMT . 17 Similarly, most of the previous studies reported significant association of lower FVC observed to predicted ratio and FEV 1 /FVC ratio with carotid IMT. 18,19 Whether the association varied by smoking status was unclear.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Most of earlier studies showed lower FEV 1 was associated with thicker IMT 3,5,8,15,18 and the presence of subclinical atherosclerosis, 3,7,10,15 However, a small study by Pike et al of 61 subjects without airflow limitation found that FEV 1 was not associated with IMT . 17 Similarly, most of the previous studies reported significant association of lower FVC observed to predicted ratio and FEV 1 /FVC ratio with carotid IMT. 18,19 Whether the association varied by smoking status was unclear.…”
Section: Discussionmentioning
confidence: 74%
“…[5][6][7][8][9][10][11] As smoking causes both chronic obstructive pulmonary disease (COPD) 12 and atherosclerosis, 13,14 some studies showed that the association between pulmonary function and atherosclerosis varied by smoking status. 5,[15][16][17] For example, the Atherosclerosis Risk in Communities (ARIC) Study showed that poor pulmonary function was significantly associated with atherosclerosis in smokers but not in never smokers. 5 Other studies, such as the Etude sur le Vieillissement Artériel study 6…”
Section: Introductionmentioning
confidence: 99%
“…A few previous studies reported that decreased pulmonary function was related to CV risk factors in non-COPD patients but had some limitations [31, 32]. …”
Section: Discussionmentioning
confidence: 99%
“…In another small study of 27 asymptomatic ex-smokers, there was no association between FEV1 and thickened carotid IMT, but worse ventilation defect percent (VDP) measured by 3 He magnetic resonance imaging (MRI) was related to carotid atherosclerosis measurements including IMT, vessel wall volume, and total plaque volume [32]. …”
Section: Discussionmentioning
confidence: 99%